Analisis Penerapan Standar Akuntansi Keuangan Entitas Mikro Kecil dan Menengah (SAK EMKM) Studi Kasus Warung Teh Dua-dua - Gunawan; Krishandayani, Vera (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
MSMES play a crucial role in Indonesia's economy, but most have not yet also adopted SAK EMKM for business actors. The purpose of this study is to explore the mechanism for preparing financial statements at Warung Teh Dua-Dua and whether it has been guided by SAK EMKM for business actors. of Warung Teh Dua-Dua is prepared and whether it has been guided by SAK EMKM, as well as identifying obstacles in its application. EMKM, as well as identifying obstacles in its application. This research applies a qualitative method with a descriptive approach, where data is collected through interview techniques, observation, and documentation. The research findings reveal that the financial statements of Warung Teh Dua-Dua are still limited to recording cash in and out and have not been guided by SAK EMKM and not yet guided by SAK EMKM. The main obstacle encountered is the lack of understanding of business actors about accounting, lack of training, and time constraints in preparing reports. time constraints on report preparation. In fact, the application of SAK EMKM can increase financial transparency and access to funding. Therefore, therefore, accounting training, utilization of simple technology, as well as support from the government so that MSMEs can implement SAK EMKM support from the government so that MSMEs can optimally implement SAK EMKM.